Host genetic susceptibility to pneumococcal and meningococcal disease: a systematic review and meta-analysis - Brouwer, Matthijs C; de Gans, Jan; Heckenberg, Sebastiaan GB; Zwinderman, Aeilko H; van der Poll, Tom; van de Beek, Diederik (The Lancet infectious diseases, 2009)
Streptococcus pneumoniae and Neisseria meningitidis can cause sepsis and meningitis. Several risk factors for pneumococcal and meningococcal disease have been identified, but the cause of basic differences in susceptibility between individuals and populations is unknown. Single-nucleotide polymorphisms are thought to explain interindividual differences in susceptibility. New technologies provide the opportunity to study the genetic basis of susceptibility to these diseases. In recent years, several studies have been published on these polymorphisms in pneumococcal and meningococcal disease, many with apparently conflicting results. Herein we provide a systematic overview of all polymorphisms studied for a relation with susceptibility to pneumococcal and meningococcal disease. We also propose an initiative to pool genetic data on pneumococcal and meningococcal meningitis in one biobank.